2023 myThaw data set - Jennika Hammar; Maybrit Goldau; Julia Boike; Moritz Rath; Norbert Anselm; Julia Martin; Sarah Chadburn; Simon Zwieback; Mathilde Carbonnel; Guillaume Herment; Stéphanie Coulombe; Mariasilvia Giamberini; et al. (PANGAEA, 2025)
The 2023 myThaw data set provides standardized measurements for permafrost thaw and the linked parameters snow depth, vegetation height and water level as suggested by Boike et al. (2021). It contains measurements from 8 circumpolar permafrost sites where data was obtained using the myThaw app which is based on the user-friendly, multiparameter protocol for standardized monitoring of permafrost thaw from 2021. The data set contains detailed metadata for each site including data on the timing of data collection, geographical coordinates and land surface characteristics (vegetation, ground surface and water features).
In: Boike, Julia; Hammar, Jennika; Goldau, Maybrit; Miesner, Frederieke; Anselm, Norbert (2024): Circumarctic seasonal measurements of permafrost parameters (thaw depth, snow depth, vegetation and tree height, water level and soil properties) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.971787